Prediction of Financial Distress Levels in State-Owned Cipta Karya Companies Using the Altman Z-Score, Springate, and Zmijewski Models - Ari Nur Wahidah; Muklis Muklis; Muhammad Fikri (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to assess the company's financial performance and analyze whether the company has the potential to experience financial distress as a precursor to bankruptcy. Predicting the level of financial distress will use the Altman Z-Score, Springate, and Zmijewski models, and look for a more accurate model among these three models. This research is descriptive quantitative in nature. The population of this research is the State-Owned/BUMN Cipta Karya company. The sampling technique in this research was purposive sampling, with several criteria. The sample for this research is the BUMN Cipta Karya company (heavy construction and civil engineering sub-sector) listed on the Indonesia Stock Exchange for the 2019-2022 period, totaling 5 companies. The results of this research show that the highest level of accuracy in predicting financial distress at State-Owned/BUMN Cipta Karya for the 2019-2022 period is Springate at 100%. Then Altman Z-Score and Zmijewski with the same level of accuracy, equal to 40%. Keywords: Financial Distress, Altman Z-Score, Springate, Zmijewski